2021
DOI: 10.3390/polym13213611
|View full text |Cite
|
Sign up to set email alerts
|

Development of Biodegradable Bio-Based Composite for Bone Tissue Engineering: Synthesis, Characterization and In Vitro Biocompatible Evaluation

Abstract: Several significant advancements in the field of bone regenerative medicine have been made in recent years. However, therapeutic options, such as bone grafts, have several drawbacks. There is a need to develop an adequate bone substitute. As a result, significant bone defects/injuries pose a severe challenge for orthopaedic and reconstructive bone tissue. We synthesized polymeric composite material from arabinoxylan (ARX), β-glucan (BG), nano-hydroxyapatite (nHAp), graphene oxide (GO), acrylic acid (AAc) throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…The multifunctional behavior of the bioactive scaffolds promotes fibronectin adsorption and integrin binding . The synergistic effect of Zn@rGO, nHAp, and the polymeric matrix increases the surface area to assist cell adhesion through the active site of bioactive scaffolds. , It can be seen that the increased Zn amount increased the cell clustering with proper cylindrical cell morphology as the time increased from 24 to 72 h. It was observed that AZG-1 has less cell clustering and AZG-4 has maximum cell clustering with proper cylindrical morphology. The increased Zn amount has shown slightly different extracellular properties with promoted multifunctional bioactive scaffold behavior.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The multifunctional behavior of the bioactive scaffolds promotes fibronectin adsorption and integrin binding . The synergistic effect of Zn@rGO, nHAp, and the polymeric matrix increases the surface area to assist cell adhesion through the active site of bioactive scaffolds. , It can be seen that the increased Zn amount increased the cell clustering with proper cylindrical cell morphology as the time increased from 24 to 72 h. It was observed that AZG-1 has less cell clustering and AZG-4 has maximum cell clustering with proper cylindrical morphology. The increased Zn amount has shown slightly different extracellular properties with promoted multifunctional bioactive scaffold behavior.…”
Section: Resultsmentioning
confidence: 91%
“…The cell morphology can also change from elongated to spherical. 44,45 In addition, the increasing contact time of the bioactive scaffolds also causes antitumor/anticancer activities. 46 The results show that the bioactive scaffolds initially promoted cell viability and later their behavior changed to antitumor/anticancer activity.…”
Section: 7mentioning
confidence: 99%
“…These polymers and GO were also crosslinked due to hydrogen bonding (H–bonding) that presents the absence peak at 1759 cm −1 and broadband at 3600–3200 cm − 1 . The increased broadband valley is due to increased intra and inter-hydrogen bonding [ 21 ]. The characteristic peaks of BC are hydroxyl, COO − , and pyranose rings.…”
Section: Resultsmentioning
confidence: 99%
“…One of the most significant features of all biomaterials is surface wettability because it depicts the true structure and chemical surface properties. Many features of therapeutic drugs, such as biocompatibility, adhesion, lubricity, selective absorption, and controlled release, are determined by wetting ( Khan et al, 2021e ). Soft hydrogels, which are made primarily of water and a hydrophilic polymeric network, are naturally hydrophilic.…”
Section: Resultsmentioning
confidence: 99%